PD-1 inhibitors in advanced esophageal squamous cell carcinoma: a survival analysis of reconstructed patient-level data - Chunyan Yan; Wenxiu Cao; Jianghua Li; Lei Zhang; Ruigang Diao (Frontiers Media S.A., 2024)
BackgroundRecently, a sum of trials of programmed cell death-1 (PD-1) inhibitors combined with chemotherapy have shown excellent efficacy compared to chemotherapy alone in patients with previously untreated, advanced esophageal squamous cell carcinoma (ESCC). However, there is no head-to-head comparison and consensus on which immunotherapy regimen results in better survival outcomes. This study aimed to evaluate the survival efficacy of various PD-1 inhibitor-based therapies in the first-line treatments for patients with advanced ESCC.MethodsData collected prior to 31 July 2023 were searched in the PubMed, Cochrane Library, Embase, Medline, and Web of Science databases. Overall survival (OS) and progression-free survival curves were pooled using the MetaSurv package. Survival data were compared by reconstructed individual patient data.ResultsA total of 4,162 patients and seven randomized controlled trials were included. After synthesizing, PD-1 inhibitors prolonged median OS from 11.3 months (95% CI (confidence interval) 10.7-11.7) to 15.6 months (95% CI 14.7-16.3). Based on reconstructed patient-level data, the toripalimab, tislelizumab, and sintilimab group achieved the longest OS, whereas the sintilimab and tislelizumab group had the lowest risk of recurrence than other treatments. In patients with a combined positive score of ≥10, sintilimab had better OS efficacy than pembrolizumab (HR: 0.71, 95% CI: 0.52-0.96). In terms of tumor proportion score of ≥1%, camrelizumab, nivolumab, and toripalimab showed proximate survival benefits in both OS and progression-free survival.ConclusionPD-1 inhibitor combined with chemotherapy significantly improved the survival time of patients with advanced ESCC. Toripalimab, tislelizumab, and sintilimab plus chemotherapy showed the best OS benefit. Longer progression-free benefits might be generated from adding tislelizumab and sintilimab to chemotherapy. Sintilimab was strongly recommended for patients with high programmed cell death-ligand 1 abundance.Systematic Review Registration:[https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42024501086].